1987
DOI: 10.1007/bf02180279
|View full text |Cite
|
Sign up to set email alerts
|

Responses to prolonged hypoxia by rainbow trout (Salmo gairdneri) I. Free amino acids and proteins in plasma, liver and white muscle

Abstract: In order to estimate the mobilization of nitrogen compounds for energetic purposes in trout under hypoxic conditions, commercial-size rainbow trout, acclimated to 15°C, were maintained for 10 weeks at an oxygen level of 5.3 ± 0.5 mg/l ('hypoxic' group) or 8.4 ± 0.4 mg/I (control group), and the changes in tissue concentrations of free amino acids and proteins studied. In animals subjected to hypoxia, there was a decrease in plasma free amino acids involved in gluconeogenesis, liver alanine and aspartic acid, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
2

Year Published

1988
1988
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 11 publications
0
8
2
Order By: Relevance
“…It has previously been suggested that a decline in plasma amino acids observed in hypoxic conditions in rainbow trout was due to an increased utilization by tissues for energy supply, for example via participation in hepatic gluconeogensis (Medale et al 1987). After 6 hours of confinement the decrease was followed by an elevation in plasma total amino acid concentration that in LR fish reached significantly higher values than HR, which only returned to pre-stress basal levels.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…It has previously been suggested that a decline in plasma amino acids observed in hypoxic conditions in rainbow trout was due to an increased utilization by tissues for energy supply, for example via participation in hepatic gluconeogensis (Medale et al 1987). After 6 hours of confinement the decrease was followed by an elevation in plasma total amino acid concentration that in LR fish reached significantly higher values than HR, which only returned to pre-stress basal levels.…”
Section: Discussionmentioning
confidence: 93%
“…High plasma amino acid levels lead to induction of liver aminotransferases and consequently the participation of these metabolites in hepatic gluconeogenesis (Morales et al, 1990;van der Boon et al, 1991;Milligan, 1997). Several studies have provided evidence that alanine constitutes a good hepatic gluconeogenic precursor in fish (Medale et al, 1987;Braley and Anderson, 1992;Vijayan et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Under this situation, an increase in liver enzymatic activities involved in amino acid catabolism (i.e. ALAT, ASAT) would be expected, because several studies have provided evidence that alanine constitutes a good hepatic gluconeogenic precursor in fish (Medale et al 1987). However, significant differences in these activities in the liver of Senegalese sole maintained under different stocking densities were not observed.…”
Section: Discussionmentioning
confidence: 99%
“…Since the increase observed was only in the enzymatic activity of GDH and not in the enzymes GOT and GPT, this finding suggests that amino acids utilized for energy in the liver of fish injected with LF‐89 and AUSTRAL‐005 were different from aspartate and alanine which can be related to the activity of GOT and GPT, respectively. In fish, α‐ketoglutarate is used as a precursor of ATP through the Krebs cycle (Arjona et al, ; Costas et al, ; Medale, Parrent, & Vellas, ; Moon & Foster, ); therefore, the greater activity of GDH in the liver of fish injected with LF‐89 and AUSTRAL‐005 could be associated with the formation of ATP from this molecule, thus playing a key energetic role during the chronic stress conditions (Herrera, Ruiz‐Jarabo, Vargas‐Chacoff, Roca, & Mancera, ; Melo & Cuamatzi, ). The gene transcription of GDH in the liver was up‐regulated only in fish inoculated with AUSTRAL‐005, suggesting that injection with AUSTRAL‐005 triggers a higher demand of energy compared with LF‐89, and this is fuelled by the amino acids (Figure b).…”
Section: Discussionmentioning
confidence: 99%
“…Since the increase observed was only in the enzymatic activity of GDH and not in the enzymes GOT and GPT, this finding suggests that amino acids utilized for energy in the liver of fish injected with LF-89 and AUSTRAL-005 were different from aspartate and alanine which can be related to the activity of GOT and GPT, respectively. In fish, α-ketoglutarate is used as a precursor of ATP through the Krebs cycle Costas et al, 2008;Medale, Parrent, & Vellas, 1987;Moon & Foster, 1995); therefore, the greater activity of GDH in the liver of fish injected with LF-89…”
Section: Vargasmentioning
confidence: 99%